Treatment of pain syndrome after aesthetic breast surgery with botulinum toxin type A - E. V. Ermilova; E. V. Zinovev; E. N. Yampolskaya (Инновационная медицина Кубани)
Objective. To justify the possibility of using botulotoxin type A for the prevention of pain syndrome after aesthetic endoprosthesis of the mammary glands.Material and Methods. The study included 72 women aged between 21 and 45 to whom were scheduled to perform breast endoprosthesis with silicone implants. All patients were divided into two groups: the first group included 38, the second group – 34 people. Two weeks before the expected date of surgery, botulotoxin type A in an amount of 100 U was injected into the patients of the first group to reduce pain syndrome in the pectoralis major muscle. Patients of the second (control) group were injected with a 0.9% NaCl solution (placebo effect) into the pectoralis major muscle. All patients underwent electroneuromyography (ENMG) to assess the denervation of the pectoralis major muscle before drug administration and two weeks after.Results. The intensity of pain syndrome was evaluated on the 1st-2nd day after surgery using a special questionnaire. In women of the first group, who were injected with botulinum toxin type A two weeks prior the intended surgery, a decrease in the intensity of the pain syndrome was observed, which in most cases allowed not to take analgesics at all. In women of the second group who were injected with a 0.9% NaCl solution, the severity of the pain syndrome reached its maximum values (according to the questionnaire), which required the prescription of analgesics, including narcotic ones, to reduce the severity of the pain syndrome. According to ENMG, when using botulotoxin type A by injecting into the pectoralis major muscle, denervation indices reached 55% compared to the initial ones, while using the saline solution, the ENMG indices did not change.Conclusion. Clinical use of botulotoxin type A injections into the pectoralis major muscle will improve the results of pain syndrome treatment after endoprosthetics of the mammary glands with implants in aesthetic surgery.